The effect of empowerment, learning organization, and organizational citizenship behavior on performance of employees - Saeful Anwar; Nina Nurani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Human resources in this case the workforce have a very important role in the Government, especially including empowerment, learning organizations, and Organizational Citizenship Behavior (OCB) on employee performance at the Wanareja Urban Village office, Subang Sub-district, Subang Regency. The purpose of the study is to find out whether empowerment, learning organization, organizational citizenship behavior (OCB) affect the performance of employees in the village. The research method uses descriptive quantitative verification. Researchers collect information by distributing questionnaires. The population of all Wanareja Urban Village office employees is 17 people. The data analysis technique used is multiple regression analysis, with the aim of knowing the strength of the relationship between variables and showing the direction of the relationship of each empowerment variable (X1), learning organization variable (X2), organizational citizenship behavior variable (X3) to Performance variable (Y ). The results of observations show that: (1) The influence of empowerment has a positive effect on employee performance with the results of 82.2%; (2) learning organization has a positive effect on employee performance with 90% results; (3) organizational citizenship behavior on employee performance with the results of 93.2%. So that employees are more flexible and responsive to the organization, allowing their employees to learn their work will definitely be better, and their performance will indirectly increase, and shows that the employee is well-behaved and his performance continues to improve.